Penerapan Hukum Ekonomi Syariah Pada Lembaga Keuangan Syariah - Fitria, Shonya Ramadhani; Khairi, Rifqil (EL-EMIR Institute, 2024)
This study aims to analyze the implementation of sharia economic law in Islamic Financial Institutions (LKS) in Indonesia, including the challenges faced and the strategies needed to improve its effectiveness. This study was conducted with a qualitative approach and used a case study method in several LKS to gain an in-depth understanding of the application of sharia principles in the operations of financial institutions. Data collection techniques include in-depth interviews with related parties, direct observation, and analysis of regulatory documentation and internal policies of LKS. The results of the study indicate that although LKS have attempted to implement sharia principles such as the prohibition of usury and gharar, there are still various challenges, including limited public understanding, limited competent human resources, and a regulatory framework that is not yet fully comprehensive. This study also identified that strengthening regulations, developing competent human resources, and better sharia governance are needed to ensure compliance and stability of LKS. Effective implementation of sharia economic law is expected to increase public trust in LKS, strengthen the stability of the financial system, and support sustainable economic growth in Indonesia.